Effects of a Physical Exercise Program (PEP-Aut) on Autistic Children’s Stereotyped Behavior, Metabolic and Physical Activity Profiles, Physical Fitness, and Health-Related Quality of Life: A Study Protocol - Ferreira, José Pedro; Andrade Toscano, Chrystiane Vasconcelos; Rodrigues, Aristides Machado; Furtado, Guilherme Eustaquio; Barros, Mauro Gomes; Wanderley, Rildo Souza; Carvalho, Humberto Moreira (Frontiers in Public Health, 2018)
Physical exercise has shown positive effects on symptomatology and on the reduction of comorbidities in populations with autism spectrum disorder (ASD). However, there is still no consensus about the most appropriate exercise intervention model for children with ASD. The Physical Exercise Program-Autism (PEP-Aut) protocol is designed to allow us to: i) examine the multivariate associations between ASD symptoms, metabolic profile, physical activity level, physical fitness and health related quality of life of children with ASD; ii) assess the effects of a 40 weeks exercise program on all these aspects of children with ASD. The impact of the exercise program will be assessed based on a sequence of the two phases. Phase 1 is a 12 weeks cross sectional study assessing the symptomatology, metabolic profile, physical fitness and physical activity levels, socioeconomic status profile, and health-related quality of life of participants. This phase is the baseline of the following phase. Phase 2 is a 48 weeks intervention study with a 40 weeks intervention with exercise that will take place in a specialized centre for children with ASD in the city of Maceió-Alagoas, Brazil. The primary outcomes will be change in the symptomatic profile and the level of physical activity of children. Secondary outcomes will be anthropometric and metabolic profiles, aerobic function, grip strength, socioeconomic status, and health-related quality of life. The study will provide critical information on the efficacy of exercise for children with ASD and help guide design and delivery of future programs.